Library Anxiety pada Mahasiswa Ilmu Perpustakaan UIN Sumatera Utara dan Universitas Sam Ratulangi Manado - Ridwan, Muhammad; Ramadhani Nalole, Suci (Media Informasi, 2025)
This study aims to analyze the phenomenon of library anxiety among Library and Information Science students of the 2023 cohort at the State Islamic University of North Sumatera (UINSU) and Sam Ratulangi University (Unsrat). The research focuses on two dominant factors causing anxiety: uncertainty in initiating information searches and confusion when navigating the library environment. Using a qualitative approach with a case study method, data were collected through in-depth interviews, observations, and documentation involving ten purposely selected informants. The findings reveal that most students experience affective and social barriers when interacting with librarians or using library systems. Feelings of embarrassment, fear of being judged as incompetent, and perceptions of librarians as overly formal reinforce students’ tendency to avoid direct interaction. Furthermore, there is a behavioral shift toward the use of artificial intelligence (AI) technologies such as ChatGPT, perceived as more practical and free from social pressure. These findings indicate that library anxiety remains a significant issue among digital-native students, leading to a decline in physical library visits and interpersonal engagement. The study highlights the need for academic libraries to design human-centered and technology-adaptive service strategies to foster inclusive, comfortable, and empowering information literacy experiences in the digital era. Key word: Library anxiety; Digital Library; anxiety; library science